Depressive Symptoms and Functionality in Older Adults of the Porto Alegre'S Primary Care - Douglas Nunes Stahnke; Renata Breda Martins; Raquel Rousselet Farias; Mara Regina Knorst; João Henrique Corrêa Kanan; Thais de Lima Resende (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: The aim of this study was to determine the prevalence of depressive symptoms (DS) and their relationship with functional, sociodemographic and anthropometric aspects in the older adults from the Family Health Strategy of Porto Alegre/ RS. METHOD: This is a cross-sectional, prospective and analytical study, with a random sample of 509 older adults from 30 public health units. The following variables were analyzed: age, age group, sex, marital status, schooling, weight, height and body mass index, functionality, activities of daily living, both basic and instrumental, and the presence of DS. For the statistical analyses, the bivariate qui-square test and the multivariate logistic regression were used. RESULTS: The prevalence of DS in this sample was 35,5%. The final model presented a significant statistical association of DS with female gender (OR = 2.87; IC95% 19.2-9.23), illiteracy (OR = 2.13; IC95% 1.89-5.12), low schooling (OR = 1.23; IC95% 1.05-2.74), dependence on IADL (OR = 4.03; IC95% 1.68-9.64), low scores in the sit-to-stand test (OR = 0.89; IC95% 0.82-0.96) and lower HGS (OR = 0.95; IC95% 0.93-0.98). CONCLUSION: The prevalence of DS observed was high (35.4%) and, considering the associations presented, it is suggested that illiterate or poorly educated, weaker and slower women with difficulty in IADL should be investigated for the presence of depressive symptoms, for being at the risk of developing them.